Exon 3 β-catenin mutations are specifically associated with colorectal carcinomas in hereditary non-polyposis colorectal cancer syndrome. (11th January 2005) - Johnson, V; Volikos, E; Halford, S E; Eftekhar Sadat, E T; Popat, S; Talbot, I; Truninger, K; Martin, J; Jass, J; Houlston, R; Atkin, W; Tomlinson, I P M; et al.
Abstract : Background and aim: Activating β-catenin mutations in exon 3 have been implicated in colorectal tumorigenesis. Although reports to the contrary exist, it has been suggested that β-catenin mutations occur more often in microsatellite unstable (MSI+) colorectal carcinomas, including hereditary non-polyposis colorectal cancer (HNPCC), as a consequence of defective DNA mismatch repair. We have analysed 337 colorectal carcinomas and adenomas, from both sporadic cases and HNPCC families, to provide an accurate assessment of β-catenin mutation frequency in each tumour type. Methods: Direct sequencing of exon 3 of β-catenin . Results: Mutations were rare in sporadic (1/83, 1.2%) and HNPCC adenomas (1/37, 2.7%). Most of the sporadic adenomas analysed (80%) were small (<1 cm), and our data therefore differ from a previous report of a much higher mutation frequency in small adenomas. No oncogenic β-catenin mutations were identified in 34 MSI+ and 78 microsatellite stable (MSI−) sporadic colorectal cancers but a raised mutation frequency (8/44, 18.2%) was found in HNPCC cancers; this frequency was significantly higher than that in HNPCC adenomas (p = 0.035) and in both MSI− (p<0.0001) and MSI+ (p = 0.008) sporadic cancers. Mutations were more common in higher stage (Dukes' stages C and D) cancers (p = 0.001). Conclusion: Exon 3 β-catenin mutations are associated specifically with malignant colorectal tumours in HNPCC; mutations appear not to result directly from deficient mismatch repair. Our data provide evidence that the genetic pathways of sporadic MSI+ and HNPCC cancers may be divergent, and indicate that mutations in the HNPCC pathway of colorectal tumorigenesis may be determined by selection, not simply by hypermutation.